Temporal muscle haematoma as a cause of suboptimal haemicraniectomy: case report - André,Charles (2003)
OBJECTIVE: To call attention to an unusual complication of decompressive haemicraniectomy in the treatment of malignant haemispheric infarction. METHOD: We describe a case in which partial decompression occurred despite large craniectomy. Complete decompression followed resection of the temporal muscle. Pertinent literature is briefly reviewed. CASE DESCRIPTION: A 55-year old woman developed massive right middle cerebral artery infarction evolving to cerebral haerniation in 40 hours. Decompressive haemicraniectomy without cortical excision was unable to revert coma and decerebrate posturing because of a massive temporal muscle haemorrhage with persistent contralateral deviation of midline structures. Muscle resection was followed by adequate external haerniation of the affected haemisphere and fast recovery. Cranioplasty was succesfully performed 22 days later, following gradual regression of cerebral oedema. CONCLUSION: There is an increasing perception of the need to operate patients with massive middle cerebral or internal carotid artery territory infarctions before the development of coma and cerebral haerniation. The most common factor leading to inadequate surgical decompression is small size craniectomy. The case reported calls attention to temporal muscle bleeding as an additional complication of craniectomy.